Iowa Birdline update, May 13-18, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for May 13-18, 1989. Highlights include the peak of Warbler migration with several species being sighted around Iowa. Epson - sheet feed/flatbed